The Role of Artificial Intelligence in Physiotherapy: A Comprehensive Review (Academia Journal of Medicine, 2023)
This paper explores the application of artificial  intelligence in the field of physiotherapy. It delves  into the various ways in which AI technologies are  revolutionizing the assessment, diagnosis, treatment,  and management of musculoskeletal and  neurological conditions. The advantages and  limitations of AI in physiotherapy are discussed,  providing a comprehensive overview of the subject.  The paper concludes with a discussion on the future  prospects and potential impact of AI on the field of  physiotherapy.
Keywords: Artificial intelligence; Physiotherapy; Musculoskeletal; Neurological; Rehabilitation